How modernization theory has stumbled in China: A political interception perspective. Issue 2 (17th February 2023) - Liu, Yu; Su, Yu-Sung; Wu, Wenquan
ABSTRACT: Economic development fails to greatly increase demand for liberal democracy in China. Is China an exception to modernization theory? If so, why? This paper studies these questions by analysing five waves of Asian Barometer Survey data from 2002 to 2019. We have three major findings. First, the shift of political values exhibits an inverted U-shaped curve with the mid-2010s as its turning point. Second, the better educated and more media exposed turned conservative much faster than the rest after the mid-2010s. Third, to trace the mechanism of this unusual reversal and divergence, we resort to a Difference-In-Differences model, taking political indoctrination, measured by media exposure and education, as treatment and the post-2013 era as treatment time, finding that political indoctrination significantly explains political cultural backsliding. Our findings enrich modernization theory by identifying the "interceptive" power of the state between economic development and cultural shifts.